1980
DOI: 10.1515/hfsg.1980.34.6.197
|View full text |Cite
|
Sign up to set email alerts
|

On the Course of Delignification During Kraft Pulping

Abstract: Keywords Kraft pulping Delignification Course of process Aryl ether cleavage Methylation Schlüsselwörter (Sachgebiete) Sulfatkochung Delignifizierung Prozeßverlauf Arylätherspaltung Methylierung On the Course of Delignification During Kraft PulpingSummary The correlation between aryl ether cleavage reactions and the initial and main (= bulk) phases of delignification during kraft pulping is supported by the behaviour of pre-methylated samples of softwood shavings. Methylation with diazomethane virtually elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 2 publications
2
65
0
Order By: Relevance
“…Veratrylglycerol--guaiacyl ether (a non-phenolic b-O-4 lignin model dimer) was synthesized by the method described by Adler et al 20 Exhaustive methylation of lignins was performed by a modification of procedures previously described. 21,22 A sample of 8 mg of lignin was dissolved in 1 mL of dioxane, and methylated with 1 mL of ethereal diazomethane (0.25 M) and 2 mL of methanol. Methylation was continued over 5 days, keeping the samples under magnetic stirring and adding 0.5 mL of fresh diazomethane per sample every 24 h. Then diazomethane was destroyed (by daylight) and solvent removed under vacuum (Speed-vac).…”
Section: Methodsmentioning
confidence: 99%
“…Veratrylglycerol--guaiacyl ether (a non-phenolic b-O-4 lignin model dimer) was synthesized by the method described by Adler et al 20 Exhaustive methylation of lignins was performed by a modification of procedures previously described. 21,22 A sample of 8 mg of lignin was dissolved in 1 mL of dioxane, and methylated with 1 mL of ethereal diazomethane (0.25 M) and 2 mL of methanol. Methylation was continued over 5 days, keeping the samples under magnetic stirring and adding 0.5 mL of fresh diazomethane per sample every 24 h. Then diazomethane was destroyed (by daylight) and solvent removed under vacuum (Speed-vac).…”
Section: Methodsmentioning
confidence: 99%
“…10 Exhaustive methylation was performed by a modification of procedures previously described. 11,12 100 mg of light petroleum-extracted straw were shaken for 7 days at room temperature in 10 mL of dioxan, and then methylated with 2.5 mL of ethereal diazomethane and 5 mL of methanol. Methylation was continued during 5 days, keeping the samples under magnetic stirring and adding 2 mL of fresh diazomethane per sample every 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…50% of total Na 2 S charge 100% of total Na 2 S charge Several authors have demonstrated that, in the initial phase of kraft delignification, the main lignin reactive structures are α-and β-ethers containing free phenolic hydroxyl groups. 26 The α-aryl ether bonds in both open and cyclic phenylcoumaran structures are readily cleaved by hydroxyl ions and the rate is independent of the hydroxide ion concentration, provided the phenolic hydroxyl group in the substrate is completely ionized. The cleavage of β-aryl ether structures (β-O-4) bonds are cleaved by hydrosulfide ions, after the conversion of that structure into the quinone methide structure by OH − .…”
Section: Impregnation Phasementioning
confidence: 99%